Between aura and access: artefactuality, institutionality, and the allure of the archival - Sommer, Tim (Anglia, 2020)
This article analyses narratives inspired by the institutional emergence of the literary archive. It focuses in particular on what historian Arlette Farge has described as the “allure of the archives”: the elusive immediacy of encounters with artefactual remnants of the past. Key to this experience is what has often been described as the ability of archival objects to conjure up the presence of their creators - a process that at the same time paradoxically depends on the uniqueness and fundamental ‘unapproachability’ of the artefact. Through regulating and restricting access to documents, the archive thus maintains their distance and simultaneously makes them available for acts of reverential consumption. Focusing on such forms of gatekeeping and consecration, the article reads Henry James’s novella “The Aspern Papers” (1888) and Martha Cooley’s novel The Archivist (1998) to enquire how the literary archive - both as an idea and as an institution - has shaped ways of thinking about the relationship between physical absence and auratic presence.